The Legal Consequences of a Married Couple as Being the Sole Founders in The Partnership - James Ridwan Efferin (Fakultas Hukum Universitas Hang Tuah, 2019)
A Partnership Firm (“Firma”) and a Limited Partnership/Commanditaire Vennootschap (“CV”) in Indonesia are regulated in the First Book of the Commercial Code of Indonesia, chapter the Third (Regarding the various Companies), in the First and Second section. Both partnerships are considered to be the special form of the civil partnership/Maatschap, which is regulated in the Civil Code of Indonesia (Article 1618 – 1652). According to Rudhi Prasetya, “In practice, it is not uncommon for us to see a Firma or CV that has only 2 partners, of which they are husband [and] wife”. Therefore the main issue will be the legitimacy of the said partnership if it has only a husband and wife as the founders/partners, especially if the said husband and wife do not make any separate marital property agreement. What will be the legal consequences if the said condition happens, especially the external liability to the third party. The main objective of this writing is to give an argumentation and the legal standing that a married couple can actually establish and be the sole founders/partners in a partnership with all of its consequences, even though they did not make any separate marital property agreement.